(untitled) (Vietnam Journal of Community Medicine, 2024)
Case introduction: We present a case of a 48-year-old female patient with metastatic cancer in the scapula, severe pain in the shoulder blade area, unresponsive to conventional painkillers. NSAID painkillers used in combination with Opioids, but the patient still has a lot of pain, VAS pain score is always 9/10. We alcohol neurolysis of suprascapular nerve, significantly reducing the patient’s pain level immediately afterward without any complications. The patient was monitored for lasting pain relief after 6 months with a VAS score of 2/10, and the patient could return to normal daily activities. Alcohol neurolysis of suprascapular nerve is a safe, effective method and can provide long-term pain relief for patients metastatic cancer to the scapula.